A REAPPRAISAL OF CONTRIBUTING FACTORS LEADING TO SHUNT INFECTION - Khan, Inayatullah; Burhan, Muhammad; Nadeem, Mohammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Central nervous shunt infection (CNSI) is a cause of significant morbidity, causing shunt malfunction and chronic ill health. It can also lead to prolong hospital stay. The aim of this study was to look into the factors responsible for neurosurgical shunt infection and measures to prevent them. Method: This retrospective case study was done with nonrandomized convenience sampling. We studied 121 patients who underwent neurosurgical shunt operations during year 1994 to 1999. These patients received pre, per and post operative antibiotics to combat shunt infection. Study design was retrospective case study with non randomized convenience sampling. Result: Out of 121 patients, 65 patients were females and 56 males. The total number of shunts procedures performed in these patients was 151. Ninety-seven patients operated once for shunt procedure. Eightythree (83) patients underwent ventriculo-peritoneal shunt, 10 patients underwent lumboperitoneal shunt, 3 had ventriculo-pleural shunt and 1 had ventriculo-atrial shunting done. Three patients developed shunt infection, only one had true primary infection. All were adults with male to female ratio of 2 to 1 and in all of them shunt was inserted first time. Conclusion: Strict aseptic technique and prophylactic use of antibiotics have critical role in the prevention of shunt infections. Keywords: CNSI, shunt infection, aseptic technique, and prophylactic antibiotics